Pengaruh Penggunaan Google Jamboard terhadap Hasil Belajar Mahasiswa Produktive Sprachfertigkeiten - Melisa Adriana Loimalitna; Juliaans E.R. Marantika; Ida C Tamaela (Universitas Pattimura, 2022)
This research aims to describes the influence of google Jamboard on the learning outcomes of students on Produktive Sprachfertigkeit Aufbaustufe A2.1 (writing skills). The research was carried out at the German department-Pattimura University,and the sample were the German learners from the 2nd semester to participate in the course Productive Language Skills Advanced Level A2.1 (Writing Skills). This research has two variables, namely Google Jamboard as an free variable and the learning outcomes as a bound variable. The research methods were experiment. The data were obtained in the first examination (pre-test) and from the second examination (post-test). The data were checked with t-test and the result of the analysis showed that t - value is greater than the t-critical value (8,40 >2,9). This means, it is a positive influence of Google Jamboard on the learning outcomes of students.